Biomass Stove Design Based Quality Function Deployment (QFD) and Design For Manufacture And Assembly (DFMA) - Yohanes Yohanes; Muhammad Idris (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2021)
This study aims to design a biomass stove as a solution for lack of LPG gas in the community in Batu Panjang, Rupat Island, Riau. The Quality Function Deployment (QFD) method is used in this study by elaborating consumer needs through public opinion needs (questionnaire survey) and elaboration of the characteristics of consumer needs. A House of Quality (HoQ) matrix was created to determine the technical characteristics for design analysis of biomass stove and designed using the Design for Manufacture and Assembly (DFMA). The result was a development of "Biomass Stove", which consists of a funnel for fuel, a fire funnel, a filter and an air chamber. The funnel chamber, which the fuel was made the insulation channel and the joining of the fire connector, forms an angle to increase the heat flow to funnel fuel and reduce the heat loss during cooking. The stove design is made safe, comfortable for users and environmentally friendly due to the existence of a filter and air chamber cover. The biomass stove was designed portable, and then it was light and easy to move around.